Valley and channel networks extraction based on local topographic curvature and k‐means clustering of contours. Issue 10 (19th October 2016) - Hooshyar, Milad; Wang, Dingbao; Kim, Seoyoung; Medeiros, Stephen C.; Hagen, Scott C.
Abstract: A method for automatic extraction of valley and channel networks from high‐resolution digital elevation models (DEMs) is presented. This method utilizes both positive (i.e., convergent topography) and negative (i.e., divergent topography) curvature to delineate the valley network. The valley and ridge skeletons are extracted using the pixels' curvature and the local terrain conditions. The valley network is generated by checking the terrain for the existence of at least one ridge between two intersecting valleys. The transition from unchannelized to channelized sections (i.e., channel head) in each first‐order valley tributary is identified independently by categorizing the corresponding contours using an unsupervised approach based on k ‐means clustering. The method does not require a spatially constant channel initiation threshold (e.g., curvature or contributing area). Moreover, instead of a point attribute (e.g., curvature), the proposed clustering method utilizes the shape of contours, which reflects the entire cross‐sectional profile including possible banks. The method was applied to three catchments: Indian Creek and Mid Bailey Run in Ohio and Feather River in California. The accuracy of channel head extraction from the proposed method is comparable to state‐of‐the‐art channel extraction methods. Key Points: An automatic method for delineating valley and channel networks is proposed The channel heads are extracted using the shape of contours The channel head identification is performed independently for each tributary